Особливості проведення польової практики з географії ґрунтів в умовах Гірського і Степового Криму - Даценко, Людмила Миколаївна; Даценко, Людмила Николаевна; Datsenko, Liudmyla; Зав’ялова, Т. В.; Zavialova, T. V.; Непша, О. В.; Nepsha, O. V.; Самек, Ю. І.; Sameek, Yu. I. (My University, 2008)
UK: Стан грунтів пов’язан з різноманіттям навколишнього середовища та впливом анторопогенного фактору, чим обумовлюється виділення категорій придатності грунтів для використання у землеробстві. EN: Field soil surveys occupy an important place in the system of training geography teachers. The skills and experience gained in this practice are used by senior students, as well as for further work in general education schools. In conducting field practice, the focus is on the methodology of field research: the proper choice of the location of the soil and geographic profile and soil cuts, the description of the soil morphological properties, as well as methods for studying the soil cover, including ground mapping issues.
Features of holiday practice from geography of soil in the conditions of girsk and step Сrimea
Keywords: польові грунтові дослідження; польова практика; рельєф; клімат; вапняк; піщаник; field practice; soil geography; soil profile; field research; soil and geographic profile; soil cut; morphological properties of soil; soil mapping